EDUCATIONAL APPROACHES TO DEVELOPING DRIBBLING SKILLS: THE INFLUENCE OF COORDINATION AND TRAINING METHODS AT KARYA MUDA FOOTBALL SCHOOL - Halim, Abdul; Bakhtiar, Syahrial; Bafirman, Bafirman; Damrah, Damrah; Ockta, Yovhandra (STKIP Singkawang, 2024)
Based on the poor dribbling abilities of SSB Karya Muda Tanjung Pinang pupils, this study was conducted. The following are the objectives of this study: (1) to compare dribbling skills trained with drill methods and small side games (SSG); (2) to compare dribbling skills with low and high coordination; (3) to compare coordination abilities with training methods; (4) to compare dribbling skills trained with drill methods and SSG; and (5) to compare dribbling skills trained with drill methods and SSG.The type of research used is quasi-experimental. Purposive sampling was used to choose the sample, which included 32 students between the ages of 9 and 12. Instruments used: dribbling test and KTK. Data were analyzed using a two-way analysis of variance (ANOVA) technique with a 2x2 factorial design. Research results: 1) There are differences in the dribbling technique abilities of students in the SSG and drill training strategy groups (p < 0.05). 2) There is a difference in the dribbling technique abilities of students in the high and low coordination groups (p < 0.05). 3) There is an interaction between training strategy and coordination (p < 0.05). 4) There are differences in the dribbling technical abilities of students in the SSG and drill strategy groups with high coordination (Qcount 15.99 < Qtable 3.85). 5) There are differences in the dribbling technical abilities of students who are given SSG and drill training strategies with coordination (Qcount 6.27 < Qtable 3.85). The study's findings show that, although having similar levels